0375 Long-term Efficacy of the Sleep to Prevent Evolving Affective Disorders (SPREAD) Trial as an Internet-based Treatment for Insomnia. (27th April 2018) - Cuamatzi-Castelan, A S; Cheng, P; Fellman-Couture, C; Tallent, G; Tran, K M; Espie, C A; Joseph, C; Roehrs, T; Drake, C L
Abstract: Introduction: A growing body of evidence supports the acute benefits of internet-based interventions for insomnia; however, the durability of the acute treatment gains from internet-based interventions has not been adequately examined. This randomized controlled-trial compared the efficacy of digital Cognitive Behavioral Therapy for Insomnia to an online attention control at post-treatment and at 12-month follow-up. Methods: 1383 subjects diagnosed with Insomnia based on DSM-5 criteria were randomized into 2 conditions: digital Cognitive behavioral Therapy for Insomnia (dCBT-I; N=946) through Sleepio or online Sleep Education control (N=440). After attrition, the final sample was 358 in the dCBT-I group and 300 in the Sleep Education group. The dCBT-I group received 6 online weekly CBT-I sessions while the control group received 6 weekly informational sleep hygiene emails. The Insomnia Severity Scale (ISI) was used as the outcome measure at three time points: pre-treatment, post-treatment and 12-month follow-up. Results: Compared to the control group, those in the dCBT-I group showed a two-fold reduction in insomnia severity (dCBT-I: -8.11 ± 0.45 SE; control: -3.87 ± 0.39 SE) at post-treatment. Importantly, these improvements were sustained at 12-month follow-up (dCBT-I: -9.96 ± 0.30 SE, control: -4.44 ± 0.26 SE). Similarly, remission T post-treatment (operationalized as ISI < 8) was also significantly higher in the dCBT-I group (53.9%) compared to the control group (14.0%), χ 2 (1) =111.5, p < .0001. The remission rate was also sustained at 12-month follow-up (dCBT-I: 46.6%, control: 17.1%). Conclusion: This study provides evidence for the long-term efficacy of dCBT-I, and supports further examination of dCBT-I as an easily accessible and low-cost alternative to face-to-face CBT-I. Support (If Any): This work is funded by the Robert Wood Johnson Foundation.